2011
DOI: 10.1128/jvi.02658-10
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Broad Neutralization of HIV-1 Subtype C by Plasma Antibodies Targeting a Quaternary Epitope Including Residues in the V2 Loop

Abstract: The targets of broadly cross-neutralizing (BCN) antibodies are of great interest in the HIV vaccine field. We have identified a subtype C HIV-1-superinfected individual, CAP256, with high-level BCN activity, and characterized the antibody specificity mediating breadth. CAP256 developed potent BCN activity peaking at 3 years postinfection, neutralizing 32 (76%) of 42 heterologous viruses, with titers of antibodies against some viruses exceeding 1:10,000. CAP256 showed a subtype bias, preferentially neutralizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
155
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(169 citation statements)
references
References 49 publications
14
155
0
Order By: Relevance
“…In particular, the conformation dependence of the DARPin-target interaction may prove advantageous for selecting potent entry inhibitors with novel specificities, including alternatives to quaternary antibodies (73,74), i.e., targeting epitopes only present on the fully assembled native envelope spike. Once identified, HIV-specific DARPin binders with inhibitory activity open multiple avenues for improving their potency.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the conformation dependence of the DARPin-target interaction may prove advantageous for selecting potent entry inhibitors with novel specificities, including alternatives to quaternary antibodies (73,74), i.e., targeting epitopes only present on the fully assembled native envelope spike. Once identified, HIV-specific DARPin binders with inhibitory activity open multiple avenues for improving their potency.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the observation that MAbs PG9 and PG16 largely recapitulate the neutralizing activity of the donor plasma provides evidence that broad neutralization can occur in some cases via a single specificity or multiple overlapping specificities (111). An overarching question from these studies concerns the number of nAb specificities that typically mediate broad plasma neutralization (72,90,95,112). Here, to gain more insights into the frequency and titer of existing bnAb specificities and possibly to identify new bnAb targets, we analyzed the specificities of plasma samples from 9 HIV-1-infected subjects who exhibited high-titer bnAbs.…”
Section: A Small Proportion Of Hiv-infected Individuals Generate a Nementioning
confidence: 99%
“…Longitudinal studies have revealed that the virus and the host nAb response continually evolve (11,73,83,86,113). After several years of infection, an estimated 10 to 30% of individuals develop bnAb responses (4,7,28,52,57,66,72,88,89). Although these extraordinary responses have little impact in the setting of established infection, they could have a major impact on transmission if they could be induced by vaccines prior to virus exposure.…”
Section: A Small Proportion Of Hiv-infected Individuals Generate a Nementioning
confidence: 99%
“…39 Broadly neutralizing antibodies that interact with quaternary neutralizing epitopes (QNE) of trimeric native Env spikes have been shown to interact with conserved aa embedded within the variable (V) loops of gp120 including the V2 loop. [40][41][42][43][44][45][46][47] Furthermore, antibodies found in individuals that exhibit potent cross-clade neutralizing activity have been shown to target conserved regions of the V1, V2, and V3 loops, providing evidence that V2 contributes to the formation of QNE that can induce potent cross-clade neutralizing antibodies. 25,43 The structure of scaffolded V1/V2 complexed with the broadly neutralizing monoclonal antibody PG9 has been resolved.…”
Section: Introductionmentioning
confidence: 99%